Single-hop all-to-all broadcast in optical star networks with breakdown or power-off transceivers. (15th October 2008) - Liu, J.C.; Ho, H-J.; Lee, S.L.
Packet scheduling provides a way to reduce routing control and guarantees overall throughput. An interesting special case of the packet scheduling is all-to-all broadcast in which every transmitter and receiver pair has exactly one packet to be transferred. Several optimal scheduling algorithms have been proposed for the all-to-all broadcast problem in wavelength division multiplexed (WDM) optical star networks. However, these algorithms do not fit anymore when failures occur in some transceivers. In this paper, we consider the all-to-all broadcast problem in WDM optical star network with some breakdown or power-off transceivers. We focus on the all-optical scheduling problem where the traffic reaches its destination in single-hop without being converted to electronic form for reaching high data transmission rates. The transmitters are tunable with an associated tuning delay, and the receivers are fixed-tuned to one of the available wavelengths. In this model, we first identify the lower bounds of the scheduling length for the problem. Then, we propose single-hop scheduling algorithms to find the optimal solution in both terms of arbitrary number of wavelengths and value of tuning latency.